Madzhab Fikih Indonesia: Akar Historis dari Arab hingga Indonesia - Ahmad Zayyadi; Wahyu Heru Pamungkas (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Indonesian fiqh are that is determined based on the personality and character of the Indonesian nation according to Hasbi as-Shiddiqi. In Indonesia, in fact, the most widely followed school of jurisprudence in Indonesia is the thought of Imam Syafii. Imam Syafii was born in Gaza (near Palestine) in 150 H and died in 204 H. The Shafii school of jurisprudence was brought by missionaries and scholars who came to Indonesia to spread Islam. After this Islamization, the indigenous clerics appeared and it was later discovered that all of them were supporters of the Shafi’i school. Hasbi Ash-Shiddieqy and several other Indonesian scholars, who are the initiators of Indonesian Fiqh, have the idea that situations and conditions such as those above have had a fairly dominant influence in the emergence of Indonesian Fiqh ideas, that the principles of Islamic law actually provide wide space for development and ijtihad- new ijtihad. The foundations of Islamic law that have been established so far, such as ijma’, qiyas, maslahah mursalah, ‘urf, and the principle of “change of law due to changes in time and place”, will actually reap discrepancies when there is no new ijtihad. The theory and method used in this article is a historical framework by using a comparative study of the Arabic madhhab and the Indonesian madzhab, thus finding a study of living fiqh with an Indonesian perspective.